Efficacy of Platelets Rich Plasma in the Management of Osteoarthritis Knee Joint Data from a Tertiary Care Hospital - Khan, Farmanullah; Saeed Ahmad; Muhammad Tahir; Awal Hakeem (ADVANCES IN BASIC MEDICAL SCIENCES, 2024)
Objective: To evaluate the efficacy of intra-articular injection of platelet-rich plasma in the management of grade 1 & 2 osteoarthritis of knee joints Methodology: This retrospective study was conducted at Khyber Teaching Hospital Peshawar, Pakistan, using clinical records of patients aged 40 to 70 years diagnosed with grade 1 and 2 knee osteoarthritis. These patients were treated with autologous intra-articular PRP injections between March 2022 and March 2024. The study included 206 patients with only type 1 and 2 osteoarthritis knee joints. No analgesic medications were used after the first month post-injection. VAS and WOMAC scores, before PRP treatment and at 3 months post-treatment were compared. Paired t-test and P value were calculated using Microsoft Excel software version 2007. Results: The study included 206 patients with grade 1 and 2 knee osteoarthritis treated with intra-articular PRP injections. Female patients were 54.36% and male patients were 45.64%. The mean age of the patients was 58.69±9 years. Most of the knees (65%) had grade II osteoarthritic while 35% of knees had grade I osteoarthritic changes. The pre-PRP injection scores were as follows: VAS score 6.75±0.9, WOMAC pain score 15.97±0.9, WOMAC stiffness score 5.29±1.1 and WOMAC Function score 58.9±6.6. The post-PRP injection scores in 3rd month were: VAS score 2.77±1.19, WOMAC pain score 8.80±1.87, WOMAC stiffness score 2.47±1.17 while WOMAC function score 22.93±5.38. No complications were observed. Conclusion: Three intra-articular PRP injections administered at one-month intervals in patients with grade 1 and 2 osteoarthritis of the knee joint resulted in a significant decrease in knee joint pain and improvement in knee joint functions, as assessed by WOMAC criteria. A limitation of our study is the lack of long-term follow-up, which prevents the evaluation of the sustained efficacy of PRP in osteoarthritis of the knee.